Research and Experiment on Electromagnetic Force Properties of LPMBLDCLM for Electromagnetic Launch - Huilai Li; Xiaomin Li; Zhiyuan Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to improve the thrust characteristics of the moving-magnet type linear permanent magnet brushless DC motor (LPMBLDCM), the structural characteristics and magnetic field are analyzed. The influence rule of electrical parameters and structural parameters on the electromagnetic properties and thrust performance are researched by finite element analysis (FEA). The effect regularity of structural parameters to mover velocity and thrust are researched as well as the electrical parameters. The LPMBLDCM system are established, and some relevant tests were taken to verify the correctness of simulation results. Simulation and experimental results show that the thrust and velocity of mover are affected by some key parameter. The results will surely provide the reference and guidance for the optimization of electromagnetic and thrust characteristics of LPMBLDCM.